2022
DOI: 10.54910/sabrao2022.54.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Rice Grain Dark Spots and Their Impact on Quality Associated Traits

Abstract: Rice grain damage due to dark spots was noted more than 10 years ago in Russia. However, this phenomenon has long existed in other rice-growing countries. The factor limiting high rice yields are insect pests and pathogenic microorganisms, the vital activity of which leads to the occurrence of dark spots on the grain shells. This study hopes to assess the effects of dark spots on rice grains of six rice cultivars bred in Russia, i.e., Rapan, Khazar, Romans, Favorit, Trio, and Prestige. The study was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…From pecky rice grain representatives, the fungal microflora"s isolation included Alternaria tenuis, Trichothecium sp., and Fusarium moniliforme; however, in small quantities in Penicillium sp., Rhizopus sp., Aspergillus flavus oryzae, Cladosporium sp., Phoma sp., and Drechslera hawaiiensis (IRRI -International Rice Research Institute, Philippines) (Fanyan et al, 2002;Kumeiko and Tumanyan, 2020). It showed that grain damage in the form of dark spots leads to varying degrees of decrease in grain quality (Tumanyan et al, 2021(Tumanyan et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…From pecky rice grain representatives, the fungal microflora"s isolation included Alternaria tenuis, Trichothecium sp., and Fusarium moniliforme; however, in small quantities in Penicillium sp., Rhizopus sp., Aspergillus flavus oryzae, Cladosporium sp., Phoma sp., and Drechslera hawaiiensis (IRRI -International Rice Research Institute, Philippines) (Fanyan et al, 2002;Kumeiko and Tumanyan, 2020). It showed that grain damage in the form of dark spots leads to varying degrees of decrease in grain quality (Tumanyan et al, 2021(Tumanyan et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Plant breeding programs aim to enhance micronutrient and antioxidant concentrations and keep low phytic acid concentrations (Bhagyawant et al, 2018). Thus, an increase in Fe and Zn content followed by a decrease in phytic acid is a valuable way to increase the bioavailability of both primary rice elements (Ha et al, 2020;Mukhina et al, 2022;Tumanyan et al, 2022). Correlation is a statistical method that can identify the association level among traits.…”
Section: Introductionmentioning
confidence: 99%